2004
DOI: 10.1016/s0301-0546(04)79231-9
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual specific immunotherapy for adults and children: a post-marketing surveillance study

Abstract: Over a one-year period, adult and child patients with a variety of type I allergies were treated with a SLIT vaccine that has shown significant efficacy and was well-tolerated with no serious or severe adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Four weeks before the onset of dysphagia, the patient had begun SLIT with ORALVAC Compact (Bencard Allergie GmbH, Munich, Germany), a commercially available treatment considered to be safe [4]. The SLIT contained specific soluble allergens (hazelnut, birch, alder) according to previous specific serum IgE testing, administered sublingually as prescribed by the manufacturer's instructions.…”
Section: Case Reportmentioning
confidence: 99%
“…Four weeks before the onset of dysphagia, the patient had begun SLIT with ORALVAC Compact (Bencard Allergie GmbH, Munich, Germany), a commercially available treatment considered to be safe [4]. The SLIT contained specific soluble allergens (hazelnut, birch, alder) according to previous specific serum IgE testing, administered sublingually as prescribed by the manufacturer's instructions.…”
Section: Case Reportmentioning
confidence: 99%
“…Overall prevalence of systemic adverse events was lower than 20% in DB-PC-RCT, whereas the prevalence of severe systemic reactions was between 1 and 2% of total recorded events [88][89][90][91][92][93]. Most commonly postmarketing surveys reported mild to moderate usually self-resolved systemic reactions [94,95].…”
Section: Safety and Tolerability Of Slit In Allergic Childrenmentioning
confidence: 99%
“…Although previous systemic reaction due to SCIT were considered as absolute contraindication for all kinds of immunotherapy, results from recent studies showed that they do not represent risk factors for further usage of other kinds of ASIT including sublingual [96]. Local adverse reactions are most common SLIT-related side effects although it is not very easy to record them as it is not usually including in postmarketing analysis nor in DB-PC-RCT [50,[85][86][87][88]. Its prevalence varies from 50 to 80% and they include oropharyngeal and gastrointestinal reactions such as itching, pruritus, and eczema in oral mucosa and/or diarrhoea, vomitus, and abdominal pain [97][98][99].…”
Section: Safety and Tolerability Of Slit In Allergic Childrenmentioning
confidence: 99%
“…82,83 The adjuvant may be injected with natural allergens or genetically linked with allergen-cDNA. 86 A ragweed-TLR-9 agonist vaccine for IT was also tested in clinical trials in allergic rhinitis patients. IL-12 has also been suggested as an adjuvant for vaccination against diseases in which the Th2 profile predominates.…”
Section: Allergen-specific Therapy With Th1-stimulating Adjuvantsmentioning
confidence: 99%